Ide Mewujudkan Masyarakat 5.0 di Indonesia: Studi Takhrij dan Syarah Hadis Kontemporer - Dary Destria; Yeni Huriani; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the obligation to study with regard to efforts to realize the idea of society 5.0 in Indonesia. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the obligation to study in the history of Ibn Majah No. 220. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for Islamic experience in an effort to realize the idea of society 5.0. This study concludes that the hadith narrated by Ibn Majah no. The relevant 220 is used as the basis for realizing the idea of society 5.0 through technological adaptation, creating happiness and well-being, and placing humans at the center. The idea of community 5.0 is not impossible to realize in Indonesia.